Slow Coronary Blood Flow: Pathogenesis and Clinical Implications - Andrea Aparicio; Javier Cuevas; César Morís; María Martín (European Cardiology Review, 2022)
Coronary slow flow (CSF) phenomenon, also known as cardiac syndrome Y, is defined as the delayed opacification of the coronary vasculature at the distal level. Different hypotheses and theories have been postulated about its substrate and mechanism, such as microvascular and endothelial dysfunction. Several studies have confirmed that CSF is a cause of ischaemia detected by non-invasive testing. Clinically, it can present as angina pectoris, acute coronary syndrome and sudden cardiac death. It has an incidence of 1–5% in patients undergoing coronary angiography and has been most frequently found in young men who are smokers with metabolic syndrome. There are no established treatments for CSF and further studies are still necessary.